INSTITUTIONS THAT FOSTER INNOVATIVE ENTREPRENEURSHIP IN BRAZIL: MAPPING AND CONNECTIONS - Carvalho, Fernanda Zambon de; Bersani, Verônica Tebas; Maldaner, Luis Felipe; Piqué, Josep Miguel (Revista Prâksis, 2020)
ABSTRACT This paper contemplates the deepening of a research conducted by the Brazilian Micro and Small Business Support Service (SEBRAE) during the 26th Anprotec Conference held in Fortaleza, state of Ceará, in the year of 2016. The research included a method to map out the needs of the Brazilian Innovation Ecosystem and covered ten institutions such as Accelerators, represented by ABRAII (Brazilian Association of Innovation and Investment Accelerators), Co-working spaces - represented by the Impact Hub. a Development Bank, FINEP (Studies and Projects Funding Agency), Anjos do Brasil; Venture Capital Investment Funds - represented by ABVCAP (Brazilian Association of Private Equity & Venture Capital), Incubators - represented by SUPERA Incubator, SEBRAE (Brazilian Micro and Small Business Support Service), Businesses - represented by Samsung Brazil and Technology Innovation Nuclei, part of Universities, represented by FORTEC (National Forum of Managers of Innovation and Technology Transfer). For this mapping, a matrix that considers the business development stage model was used to identify key actions and gaps in innovative entrepreneurship fostering in Brazil, also taking five critical business development variables into consideration - technology, talent, finance, location, and evolution. The results point to recurrences and lack of support and contribute with proposals for the Brazilian innovation ecosystem. Keywords: Innovative entrepreneurship. Innovation ecosystem. Network of institutions. RESUMO Este artigo contempla o aprofundamento de uma pesquisa realizada pelo Serviço Brasileiro de Apoio às Micro e Pequenas Empresas (SEBRAE) durante a 26ª Conferência Anprotec, realizada em Fortaleza, Ceará, no ano de 2016. A pesquisa incluiu um método para mapear as necessidades do Ecossistema Brasileiro de Inovação e cobriu dez instituições tais como Aceleradoras, representadas pela ABRAII (Associação Brasileira de Aceleradoras de Inovação e Investimento), Espaços de Co-working, representadas pelo Impact Hub, um Banco de Desenvolvimento, FINEP (Financiadora de Estudos e Projetos), Anjos do Brasil; Fundos de Investimento em Venture Capital, representada pela ABVCAP (Associação Brasileira de Private Equity & Venture Capital), Incubadoras, - representada pela SUPERA Incubadora, SEBRAE (Serviço Brasileiro de apoio às Micro e Pequenas empresas), Empresas - representadas pela Samsung Brazil e o NIT (Núcleo de Inovação e Tecnologia das Universidades), representado pela FORTEC (Forum Nacional de gerentes de Inovação e Transferência de Tecnologia). Para esse mapeamento, uma matriz que considera o modelo de estágio de desenvolvimento de negócios foi utilizada para identificar as principais ações e lacunas no fomento ao empreendedorismo inovador no Brasil, levando em consideração cinco variáveis críticas de desenvolvimento de negócios - tecnologia, talentos, finanças, localização e evolução. Os resultados apontam para recorrências e falta de apoio e contribuem com propostas para o ecossistema brasileiro de inovação. Palavras-chave: Empreendedorismo Inovador. Ecossistema de inovação. Rede de Instituições.